Health among retired Great Britain`s olympic athletes: A cross-sectional study of disease and multimorbidity - Cooper, D. J.; Sim, J. (Sports Medicine - Open, 2025)
Background Currently, there is a paucity of long-term health data for retired athletes. This study describes the prevalence of common morbidities and multimorbidity among retired Great Britain`s (GB) Olympic athletes, compared to a general population comparator group.